Transcatheter Versus Surgical Aortic Valve Replacement in Patients With Prior Coronary Artery Bypass Grafting: Trends in Utilization and Propensity-Matched Analysis of In-Hospital Outcomes. (April 2018) - Gupta, Tanush; Khera, Sahil; Kolte, Dhaval; Goel, Kashish; Kalra, Ankur; Villablanca, Pedro A.; Aronow, Herbert D.; Abbott, J. Dawn; Fonarow, Gregg C.; Taub, Cynthia C.; Kleiman, Neal S.; Weisz, Giora; et al.
Abstract : Background—: A significant proportion of patients requiring aortic valve replacement (AVR) have undergone prior coronary artery bypass grafting (CABG). Reoperative heart surgery is associated with increased risk. Data on relative utilization and comparative outcomes of transcatheter (TAVR) versus surgical AVR (SAVR) in patients with prior CABG are limited. Methods and Results—: We queried the 2012 to 2014 National Inpatient Sample databases to identify isolated AVR hospitalizations in adults with prior CABG. In-hospital outcomes of TAVR versus SAVR were compared using propensity-matched analysis. Of 147 395 AVRs, 15 055 (10.2%) were in patients with prior CABG. The number of TAVRs in patients with prior CABG increased from 1615 in 2012 to 4400 in 2014, whereas the number of SAVRs decreased from 2285 to 1895 ( P trend <0.001). There were 3880 records in each group in the matched cohort. Compared with SAVR, TAVR was associated with similar in-hospital mortality (2.3% versus 2.4%; P =0.71) but lower incidence of myocardial infarction (1.5% versus 3.4%; P <0.001), stroke (1.4% versus 2.7%; P <0.001), bleeding complications (10.6% versus 24.6%; P <0.001), and acute kidney injury (16.2% versus 19.3%; P <0.001). Requirement for prior permanent pacemaker was higher in the TAVR cohort, whereas the incidence of vascular complications and acute kidney injury requiring dialysis was similar in the 2 groups. Average length of stay was shorter in patients undergoing TAVR. Conclusions—: TAVR is being increasingly used as the preferred modality of AVR in patients with prior CABG. Compared with SAVR, TAVR is associated with similar in-hospital mortality but lower rates of in-hospital complications in this important subset of patients. Abstract : Supplemental Digital Content is available in the text.